2013
DOI: 10.1155/2013/153045
|View full text |Cite
|
Sign up to set email alerts
|

Snake Venom PLA2s Inhibitors Isolated from Brazilian Plants: Synthetic and Natural Molecules

Abstract: Ophidian envenomation is an important health problem in Brazil and other South American countries. In folk medicine, especially in developing countries, several vegetal species are employed for the treatment of snakebites in communities that lack prompt access to serum therapy. However, the identification and characterization of the effects of several new plants or their isolated compounds, which are able to inhibit the activities of snake venom, are extremely important and such studies are imperative. Snake v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 73 publications
1
47
0
4
Order By: Relevance
“…Antioxidants interrupt free radical chain oxidation by donating hydrogen from hydroxyl groups to form a stable end product, diphenylpicrylhydrazine (DPPH), which does not initiate or propagate further oxidation of lipids. This causes the purple-coloured DPPH to lose its chromophore and turn it into a yellowish product (α,α-diphenyl-β-picryl hydrazine) [63][64][65].…”
Section: Antioxidant Activity Of O Stamineus and P Niruri Extractsmentioning
confidence: 99%
“…Antioxidants interrupt free radical chain oxidation by donating hydrogen from hydroxyl groups to form a stable end product, diphenylpicrylhydrazine (DPPH), which does not initiate or propagate further oxidation of lipids. This causes the purple-coloured DPPH to lose its chromophore and turn it into a yellowish product (α,α-diphenyl-β-picryl hydrazine) [63][64][65].…”
Section: Antioxidant Activity Of O Stamineus and P Niruri Extractsmentioning
confidence: 99%
“…An aqueous extract of Mandevilla velutina was an effective inhibitor of phospholipase A 2 and inhibited some of its toxic effects, such as hemorrhage [19]. Carvalho et al (2013) [3] reported the importance of plant species in treating snakebites, especially in places that do not have access to serotherapic treatment.…”
Section: Phospholipase A2 Activitymentioning
confidence: 99%
“…These substances might also act by inhibiting the action of phospholipases from various sources, both animal and human, exerting anti-inflammatory activities and interfering in processes such as blood coagulation and platelet aggregation. These processes are closely related to the action of eicosanoids generated from arachidonic acid, one of the products of the breakdown of phospholipids [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are a few studies on genotoxicity evaluations, the effect on phospholipase or even potential anti-snakebite activities of the essential oils or their constituents, highlighting a wide range of studies to be explored [8] [9] [10].…”
Section: Introductionmentioning
confidence: 99%